2020
DOI: 10.5863/1551-6776-25.6.528
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation Analysis of Aprepitant Pharmacokinetics in Pediatric Patients With Postoperative or Chemotherapy-Induced Nausea and Vomiting

Abstract: OBJECTIVES Aprepitant is effective for the prevention of chemotherapy-induced or postoperative nausea and vomiting (CINV/PONV). The aim of this study was to develop a population pharmacokinetic (PK) model of aprepitant in pediatric patients and to support dosing recommendations for oral aprepitant in pediatric patients at risk of CINV. METHODS A population PK model was constructed based on data from 3 clinical studies in which children (6 months to 12 years) and adolescents (12–19 years) were treated with a 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In line with the published model of Chain et al, 8 maturation was tested as covariate on CL, but this did not improve our model. In addition, no trend for an age effect was found looking at (ETA) plots.…”
Section: Model Development and Evaluationsupporting
confidence: 56%
See 2 more Smart Citations
“…In line with the published model of Chain et al, 8 maturation was tested as covariate on CL, but this did not improve our model. In addition, no trend for an age effect was found looking at (ETA) plots.…”
Section: Model Development and Evaluationsupporting
confidence: 56%
“…This is also in accordance with previous literature. 8,20 However, both previous studies used lag-time to correct for the delayed absorption, which represents an abrupt increase in the absorption rate from a value of zero. From a physiological approach, one would expect a rather slow increase starting from time point zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosing schedules result in comparable systemic exposures as seen in adults, but with lower CINV control than reported in adult trials. 15,18 The use of aprepitant and fosaprepitant is limited by their properties as moderate CYP3A4 inhibitors, and they have the potential to increase the AUC of CYP3A4 sensitive substrates, including many antineoplastic agents, by up to five-fold. 3 A systematic review identified clinically significant pharmacokinetic interactions between aprepitant/ fosaprepitant and the antineoplastic agents bosutinib, cabazitaxel, and cyclophosphamide and adverse events when aprepitant/ fosaprepitant was co-administered with ifosfamide.…”
Section: -Ht 3 Receptor Antagonistsmentioning
confidence: 99%
“…Recommendations on doses are complicated by lack of paediatric pharmacokinetic studies, and children's doses cannot always be extrapolated from adult studies. 14,15,18 Optimal acute CINV control is the most crucial factor to prevent anticipatory and delayed CINV, 8 but effective antiemetic strategies must be available to manage CINV in these phases too. POGO has developed guidelines for breakthrough, refractory, and anticipatory CINV in children, but the recommendations within these guidelines are generally weak.…”
Section: Adherence To Available Antiemetic Guidelinesmentioning
confidence: 99%